ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) DI KABUPATEN KLATEN - Arwani Windyas; Muhammad Hasan Ma’ruf; Wikan Budi Utami (JURNAL WIRANOMIKA, 2025)
This research was conducted with the aim to determine user engagement, education and traininng programs, personal skills and training programs, persnonal skills and high technology. This research was conducted at PDAM Klaten Regency with a total sample of 50. This type of research is quantitative and based on primary data. Sampling technique using saturated sampling method. Methods of data collection with a list of questions data analysis methode using descriptive statistics, validity test, reliability test and classic assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test. Testing the hypothesis using the F test, t test, and test the coefficient of determination. The results of this study are partial user involvement does not affect the performance of accounting information systems, educational programs and educational levels are not affect the performance of accounting information systems, personal technical skills do not affect the performance of accounting information systems and above management support has a significant impact on accounting information systems.